2014
DOI: 10.1155/2014/185716
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Antioxidant and Anti‐Skin‐Aging Activities of Ethyl Acetate Extraction from Idesia polycarpa Defatted Fruit Residue in Aging Mice Induced by D‐Galactose

Abstract: Two different concentrations of D-galactose (D-gal) induced organism and skin aging in Kunming mice were used to examine comprehensively the antioxidant and antiaging activities of ethyl acetate extraction (EAE) from Idesia polycarpa defatted fruit residue for the first time. The oxygen radical absorbance capacity (ORAC) of EAE was 13.09 ± 0.11 μmol Trolox equivalents (TE)/mg, which showed EAE had great in vitro free radical scavenging and antioxidant activity. Biochemical indexes and morphological analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
32
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 28 publications
(34 reference statements)
6
32
0
2
Order By: Relevance
“…This strain not only increased serum SOD and GSH-Px activities as well as total antioxidative capacity in a dose-dependent manner, but also augmented hepatic and splenic protein expression of Cu/Zn-SOD and Mn-SOD in mice treated with D-galactose (Suo et al, 2018). As previously reported, Cu/Zn-SOD and Mn-SOD were the main antioxidant gatekeepers that could scavenge superoxide anion (Wouters et al, 2013), while activation of Cu/Zn-SOD decreased oxidative stress-induced hepatic collagen and damage (Ye, Jia, Tang, & Chen, 2014). Since butyrate can provide nicotinamide adenine dinucleotide phosphate (NADPH) for the formation of GSH, probiotics also enhanced antioxidant capacities by producing butyrate (Heshmati et al, 2018).…”
Section: Anti Oxidative Ac Tivit Y Of Prob Iotic Ssupporting
confidence: 69%
“…This strain not only increased serum SOD and GSH-Px activities as well as total antioxidative capacity in a dose-dependent manner, but also augmented hepatic and splenic protein expression of Cu/Zn-SOD and Mn-SOD in mice treated with D-galactose (Suo et al, 2018). As previously reported, Cu/Zn-SOD and Mn-SOD were the main antioxidant gatekeepers that could scavenge superoxide anion (Wouters et al, 2013), while activation of Cu/Zn-SOD decreased oxidative stress-induced hepatic collagen and damage (Ye, Jia, Tang, & Chen, 2014). Since butyrate can provide nicotinamide adenine dinucleotide phosphate (NADPH) for the formation of GSH, probiotics also enhanced antioxidant capacities by producing butyrate (Heshmati et al, 2018).…”
Section: Anti Oxidative Ac Tivit Y Of Prob Iotic Ssupporting
confidence: 69%
“…Both Cu/ Zn-SOD and Mn-SOD are antioxidant gatekeepers and scavenge superoxide anion and other radicals (Wouters et al, 2013). Activation of Cu/Zn-SOD reduced oxidative stress induced accumulation of hepatic collagen (Ye et al, 2014), and oxidative damage and inflammation in mice (Zhang et al, 2007). Thus, LPSP-YBJ01 strain can reduce d-galactose-induced oxidative damage in livers of oxidation mice.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, to the best of our knowledge, the effects of RHL on oxidative stress and aging-associated gene expression have been investigated for the first time in an animal model, using chronic administration of D-gal to induce The kidney and liver are important organs for detoxification; however, their functions gradually decline due to age-associated structural atrophy (12). The present results indicated that the kidney and liver were atrophied in D-gal-induced aging mice.…”
Section: Discussionmentioning
confidence: 99%
“…D-gal injection has since been widely used to establish a model for anti-aging research (10)(11)(12)(13). D-gal, a reducing sugar, is a naturally occurring substance in the body, which is completely metabolized at normal concentrations.…”
Section: Introductionmentioning
confidence: 99%